Interval cancer after colonoscopy in the Austrian National Screening Programme: influence of physician and patient factors. Issue 7 (6th October 2020) - Waldmann, Elisabeth; Penz, Daniela; Šinkovec, Hana; Heinze, Georg; Rinner, Christoph; Jiricka, Lena; Majcher, Barbara; Hinterberger, Anna; Trauner, Michael; Ferlitsch, Monika
Abstract : Objective: Postscreening colorectal cancer (PSCRC) after screening colonoscopy is associated with endoscopists' performance and characteristics of resected lesions. Prior studies have shown that adenoma detection rate (ADR) is a decisive factor for PSCRC, but correlations with other parameters need further analysis and ADR may change over time. Design: Cohort study including individuals undergoing screening colonoscopy between 1/2008 and 12/2019 performed by physicians participating in a quality assurance programme in Austria. Data were linked with hospitalisation data for the diagnosis of PSCRC (defined as CRC diagnosis >6 months after colonoscopy). ADR was defined dynamically in relation to the time point of subsequent colonoscopies; high-risk groups of patients were those with an adenoma ≥10 mm, or with high-grade dysplasia, or villous or tubulovillous histology, or a serrated lesion ≥10 mm or with dysplasia, or colonoscopies with ≥3 lesions. Main outcome was PSCRC for each risk group (negative colonoscopy, hyperplastic polyps, low-risk and high-risk group of patients) after colonoscopy by endoscopists with an ADR <20% compared with endoscopists with an ADR ≥20%. Results: 352 685 individuals were included in the study (51.0% women, median age 60 years) of which 10.5% were classified as high-risk group. During a median follow-up of 55.4 months, 241 (0.06%) PSCRC were identified; of 387 participating physicians, 19.6% had at least one PSCRC (8.4% two or more). While higher endoscopist ADR decreased PSCRC incidence (HR per 1% increase 0.97, 95% CI 0.95 to 0.98), affiliation to the high-risk group of patients was also associated with higher PSCRC incidence (HR 3.27, 95% CI 2.36 to 4.00). Similar correlations were seen with regards to high-risk, and advanced adenomas. The risk for PSCRC was significantly higher after colonoscopy by an endoscopist with an ADR <20% as compared with an endoscopist with an ADR ≥20% in patients after negative colonoscopy (HR 2.01, 95% CI 1.35 to 3.0, p<0.001) and for the high-risk group of patients (HR 2.51, 95% CI 1.49 to 4.22, p<0.001). Conclusion: A dynamic calculation of the ADR takes into account changes over time but confirms the correlation of ADR and interval cancer. Both lesion characteristics and endoscopists ADR may play a similar role for the risk of PSCRC. This should be considered in deciding about appropriate surveillance intervals in the future.